Controllable Preparation of Porous Polypropylene Piezoelectrets Using Crystallization Self‐Reinforcement Method Induced by the Variable Thermal History. Issue 9 (10th July 2022) - Xu, Jiahui; Xu, Linjie; Zheng, Na; Yang, Jiang; Jiang, Ziyin; Zhang, Cailiang; Yao, Zhen; Tang, Longcheng; Cao, Kun
Abstract: A porous linear isostatic polypropylene ( i PP) piezoelectret with oriented cell structure is controllably prepared by crystallization self‐reinforcement method based on a unique variable thermal history. In this multi‐step one‐pot foaming strategy, the i PP sheet placed in a 1D confined space undergoes appropriate initial heating, quenching, reheating, and pressure relief process assisted with supercritical CO2 (scCO2 ). The crystallization self‐reinforcement of i PP is realized by inducing the formation of closely packed crystals, whose residual lamellae in the melt serve as the nodes to enhance the melt strength during reheating. The above closely packed lamellae are used as the heterogeneous nucleating cell sites as well as the crystal nuclei in the CO2 relief process. This makes the cells easier to deform in a 1D restricted space and form uniformly oriented cells. Furthermore, the static piezoelectric coefficient of the porous i PP piezoelectret with the optimal expansion ratio and orientation ratio of 18.8 and 6.6 is 700 pC/N, reaching 1.5 times that of commercial porous PP piezoelectret. Moreover, piezoelectric energy harvester made with porous i PP piezoelectret can light up 22 LED lights arranged in ZJU word. Therefore, the novel foaming strategy provides a new insight for uniform preparation of the polymer foams with oriented cells. Abstract : A porous i PP piezoelectret with oriented cell structure is controllably prepared by a crystallization self‐reinforcement one‐pot method assisted with scCO2 . The closely packed lamellae are induced by the 1D‐restricted variable thermal history and improve foamability. The obtained piezoelectret has d33 of up to 700pC/N and can light up 22 LEDs.